(untitled) (Academia Journal of Medicine, 2019)
Background: The incidence of invasive pneumococcal disease in children has come down because of polysaccharide vaccine. The increased incidence of bacteremia among young children may be due to part of maturational immune deficiency in the production of opsonic Ig Ganti bodies to the polysaccharide antigens present on en capsulated bacteria. Fever is a common present in gsymp to min paediatric out patient practice and in children less 3 years of age. Approximately 20%to30% of the children may have no identifiable cause off ever after history and physical examination. Subjects and Methods: Children in the age group of 1-3 years presenting to the outpatient department were screened for temperature >39°C and who satisfied inclusion criteria were included in the study. Temperatures were recorded either in the axillary or rectal areas. Informed consent was obtained from parents or guardian & clearance of Institutional Ethical Committee Review Board. Blood samples were taken for total WBC count, ANC, ESR and CRP and at the same time samples for blood culture. Blood cultured in various media incubated overnight and colony morphology was read. Results: CRP >6mg/d1 was observed in 25 cases of children who had SBI giving rise to sensitivity of 75.8%, 46 children who did not have SBI have CRP <6mg/d1 giving a specificity of 39.3%. Among 96 cases with CRP more than 6mg/d1 only 25 (26%) cases had SBI giving PPV of 26%. Among 54 cases of CRP <6mg/d1 46(85%) cases did not have SBI giving a NPV of 85.2%. Conclusion: CRP determines more selective strategy for children with SBI for additional diagnostic studies and appropriate antibiotic therapy.